Redes socioassistenciais e atendimento à pessoa idosa: uma análise da proteção social em um município de médio porte - Campos, Michelle de Cassia (2023)
Longevity brings important challenges for society, especially with regard to ensuring a better quality of life for the older adults. The social and family support network are proven relevant factors for reducing the risk of frailty and mortality. This study aimed to analyze the relationship between sociodemographic conditions, family structure and social support networks and to analyze the perception, care, reception offered by social assistance equipment and the representativeness of these services for the older adults, in a municipality of the state of Minas Gerais. This is a cross-sectional, observational, descriptive study with a quantitative and qualitative approach, based on the assumptions of the concomitant mixed method of investigation. The study included 80 people aged 60 years or over, of both sexes, users of the social assistance services of the CRAS and CREAS in the municipality. For data collection, semi-structured interviews were carried out in face-to-face format, and the following instruments were applied: genogram, ecomap and Tilburg frailty indicator and minimal map of relationships. According to the results obtained, the highest percentage of participants are female aged between 60 and 70 years, white, married, with low education, retired, with income up to one minimum wage. The results show us that 78.75% of respondents have children and 47.50% live in households with up to two members. The highest percentage of respondents has frailty and the physical domain stands out; have a close relationship with people who live in the same home and the highest density of the support network is centered on the family, it was found that although all respondents are users of social assistance services and responded positively when asked about reception and the representativeness of these services, does not identify them as a support network. It is concluded, therefore, that it is necessary to advance in the social support offered to the older adults, to broaden our perception of their physical, emotional and psychological needs. Public policies aimed at this population urgently need to be reformulated so that longevity also means quality of life.